Bullying, Psychological, and Physical Trauma During Early Life Increase Risk of Major Depressive Disorder in Adulthood: A Nationwide Community Sample of Korean Adults - Kim, Hyun Soo; Pyo, Hong Jin; Fava, Maurizio; Mischoulon, David; Park, Mi Jin; Jeon, Hong Jin (Frontiers in Psychiatry, 2022)
ABSTRACT Background: There is an association between early life traumas and the development of depression in adults. Few studies have used nationwide population-based samples to investigate whether the type of early life trauma differentially influences the risk of developing depression. Methods: Major depressive disorder and early life trauma were assessed using the Korean version of the Composite International Diagnostic Interview (K-CIDI) for DSM-IV psychiatric disorder and a questionnaire for early life trauma in the Korean Epidemiological Catchment Area Study in 2016. A total of 4652 participants were included in the final analysis. This study evaluated the effect of the type and frequency of reported early life trauma on the risk of developing MDD and the association between reported early life trauma and differential symptoms of MDD. Results: Individuals with reported early life trauma had a 3.7-fold increased risk of MDD. The risk of MDD was associated with bullying trauma (odds ratio (OR) = 1.847, p = .005) after adjusting for age, gender, marriage, job, and education years. The risk of MDD was increased as the types of reported early life traumas increased. Conclusions: Bullying trauma during early life represents a risk factor for MDD, especially in individuals exposed to multiple traumas in early life.